Chemical Characteristics of Stack Particulate Matter Emitted from Sintering Process of an Integrated Steel Mill and Resolution of Source Contributors on Boundary PM2.5 - Cheng-Tsung Shao; Yu-Lun Tseng; Chung-Shin Yuan; Wen-Hsi Cheng; Nian-Jie Li; Jia-Yi Zhao (Aerosol and Air Quality Research)
Abstract Background This study investigated the chemical characteristics of PM2.5 emitted from the sintering process of an integrated steel mill and assesses the contribution of emission sources to boundary PM2.5. Methods PM2.5 samples were simultaneously collected from three stacks of the sintering process and two boundary sites located at the upstream (Site N) and downstream (Site S) of the steel mill. The chemical compositions of PM2.5, including water-soluble ions (WSIs), metallic elements, carbonaceous matter, anhydrosugars, and organic acids, were further analyzed. The chemical mass balance (CMB) receptor model was then employed to identify emission sources and quantify their contributions. Results and Discussion Stack emissions revealed that the dominant anions (SO4 2−, NO3 −, Cl−) and cations (Na+, NH4 +, and Ca2+) were similar across TPM, FPM, and CPM fractions. Fe, Al, and Ca were the most abundant metals, while organic carbon (OC) dominated the carbonaceous content, primarily from coke oven gas and solid fuel combustion. At the boundary sites, PM2.5 concentrations were generally higher at Site S, especially in fall and winter, due to fugitive dust from raw material handling and heavy-duty truck activities. Seasonal variation of PM2.5 concentrations followed the order: winter > fall > spring > summer. Dominant WSIs included NO3 −, SO4 2−, NH4 +, Cl−, and Na+, and the key metals were Fe, Ca, Mg, Al, and Zn. The OC/EC ratios ranged from 1.49–1.88 and were slightly higher at Site N. Source apportionment showed that the steel mill contributed 28.3% and 36.6% of PM2.5 at Sites N and S, respectively, with the sintering process being the largest contributor (3.37% at Site N and 12.4% at Site S). Conclusions The sintering process in the integrated steel mill significantly influenced PM2.5 composition and boundary air quality, especially at the downwind site. The findings highlighted the importance of emission control measures targeting sintering operations and material handling to mitigate PM2.5 pollution. Graphical abstract